2014
DOI: 10.1158/1538-7445.am2014-2938
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2938: Synergistic effects of properly timed HPV16 synthetic long peptide vaccination during standard carboplatin-paclitaxel chemotherapy in animals and in patients with metastatic cervical carcinoma

Abstract: We previously developed a synthetic long overlapping HPV16 E6/E7 peptides (HPV16-SLP) vaccine that was clinically active in patients with HPV16+ high-grade vulvar intraepithelial neoplasia. Complete lesion regression was related to a strong vaccine-prompted HPV16-specific effector T-cell response. However, in patients with HPV16-induced metastatic cervical cancer the vaccine-induced T-cell responses were weaker and did not result in clear clinical benefit. A new study on the immune constitution of PBMC of such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…An experimental study reported that carboplatin-paclitaxel chemotherapy in the HPV16 + mouse tumor model increased the frequency of myeloid cells in the circulatory and TME. Combining chemotherapy with ISA101 in patients with metastatic cervical cancer and HPV16 + mouse tumor model improved anti-tumor immune responses via depletion of myeloid cells and modulation of immunosuppressive TME ( 65 ). Another study also demonstrated that carboplatin/paclitaxel chemotherapy could deplete immunosuppressive myeloid cells, improving HPV-16-specific T cells and increasing the effectiveness of ISA101 and tumor regression in patients with HPV-16-induced cervical cancer ( 12 ).…”
Section: Combination Therapies With Isa101mentioning
confidence: 99%
“…An experimental study reported that carboplatin-paclitaxel chemotherapy in the HPV16 + mouse tumor model increased the frequency of myeloid cells in the circulatory and TME. Combining chemotherapy with ISA101 in patients with metastatic cervical cancer and HPV16 + mouse tumor model improved anti-tumor immune responses via depletion of myeloid cells and modulation of immunosuppressive TME ( 65 ). Another study also demonstrated that carboplatin/paclitaxel chemotherapy could deplete immunosuppressive myeloid cells, improving HPV-16-specific T cells and increasing the effectiveness of ISA101 and tumor regression in patients with HPV-16-induced cervical cancer ( 12 ).…”
Section: Combination Therapies With Isa101mentioning
confidence: 99%